2022
DOI: 10.12998/wjcc.v10.i1.227
|View full text |Cite
|
Sign up to set email alerts
|

Zinc carnosine-based modified bismuth quadruple therapy vs standard triple therapy for Helicobacter pylori eradication: A randomized controlled study

Abstract: BACKGROUND Helicobacter pylori ( H. pylori ) infection is a worldwide problem with increasing burden on the health sector due to its increasing rate of resistance. The conventional triple therapy (TT) is becoming obsolete with a high failure rate of eradication, necessitating the need for better alternatives or regimens. AIM To investigate H. pylori eradication rate of TT vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Accordingly, PZN regimen can be effectively used for H. pylori with an ITT H. pylori eradication rate of 80.4%. Moreover, in a recent RCT, PZN was adjunctly used with the bismuth quadruple therapy achieving an H. pylori eradication rate of 93.5%, which was statistically significant in comparison with the triple therapy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, PZN regimen can be effectively used for H. pylori with an ITT H. pylori eradication rate of 80.4%. Moreover, in a recent RCT, PZN was adjunctly used with the bismuth quadruple therapy achieving an H. pylori eradication rate of 93.5%, which was statistically significant in comparison with the triple therapy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, polaprezinc (PZN), a zinc-L-carnosine complex ( Figure 1 ) [ 23 ], has promising properties as an antioxidant promoting ulcer healing and mucosal protective agent to counteract various clinical conditions in animals and human studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Furthermore, PZN can function by ameliorating inflammation [ 33 ], preventing apoptosis [ 34 ], and protecting tight junctions.…”
Section: Introductionmentioning
confidence: 99%
“…Polaprezinc (PZN) or zinc carnosine (L-carnosine) are zinc chelate compounds that protect the digestive mucosa ( Mahmoud et al, 2022 ). This antioxidant compound is particularly efficient in protecting against H. pylori and promoting ulcer healing, and unlike other antibiotics, it does not cause drug resistance ( Teng et al, 2020 ; Ibrahim et al, 2022 ; Mahmoud et al, 2022 ). PZN has been shown in several trials to be useful in reducing apoptosis and inflammation, healing skin and stomach wounds, and preserving tight junctions ( Furihata et al, 2020 ; Ibrahim et al, 2022 ).…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…A very recent randomized controlled study that was carried out by Ibrahim and collaborators demonstrated that 10 days of modified bismuth quadruple therapy fortified with polaprezinc (also known as zinc carnosine) was more effective than 14 days of conventional triple therapy in eradicating H. pylori infection, without additional significant adverse events [ 257 ]. Of note, a different recent study employing polaprezinc-loaded antioxidant electrospun membrane demonstrated the ability of this formulation to up-regulate the Nrf2/HO-1/SOD-1 signaling molecules in a concentration-dependent manner [ 258 ].…”
Section: The Therapeutic Potential Of Carnosine As An Antidote In Pre...mentioning
confidence: 99%